Clinical characteristics and MRI-based phenotypes of perianal abscess formation in children with fistulizing Crohn's Disease - Tabari, Azadeh; Kaplan, Jess L.; Huh, Susanna Y.; Moran, Christopher J.; Gee, Michael S. (Frontiers in Pediatrics, 2022)
Purpose: The aim of this study was to explore potential correlation of the MR imaging features and clinical characteristics with formation of perianal abscess in children with Crohn’s perianal fistulas (CPF). Methods: From 2010 to 2020, 60 patients with CPF (F:M 17:43, mean age 11.1±4 years, ranging 3-18 years) were identified retrospectively. Patients were categorized into two groups based on presence or absence of perianal abscess. Baseline clinical and MRI characteristics were recorded for each patient. All the statistical calculations were performed using R (version 3.6.3). Results: A total of 44 abscesses were identified in 36 children (mean volume 3 ± 8.6 mL, median 0.3 mL), with 24 patients having perianal disease without detectable abscess on MRI. Ten patients (28%) showed perianal abscess on pelvic MRI at the initial diagnosis. The rate of active disease on colonoscopy (visible ulcerations/aphthous ulcers) was similar in both groups (95% vs. 94%). With regards to disease location, the majority of patients (40/60, 66.6%) in both groups had ileocolonic CD. All patients without abscess had a single perianal fistula (n= 24; 3 simple and 21 complex fistulae), however, patients with perianal abscess tended to have >1 fistulous tracts (n= 50 fistulas; all complex, 27 single, 10 double and 1 triple). Intersphincteric fistula was the most common fistula type in both groups (79% and 66%, p= 0.1). The total length of fistula (3.8 ± 1.7 vs. 2.8 ± 0.8 cm, p= 0.006) and presence of multiple external openings (n= 25 vs. 7, p= 0.019) were significantly higher in patients with abscesses, and fistula length >3.3 cm showed 80% specificity and 83% PPV for the presence of perianal abscess. Fistulas were symptomatic (pain, bleeding or drainage) at similar rates in both groups (68% and 70%, p= 0.1). Conclusion: Pediatric patients with CPF who develop perianal abscess have a distinct imaging phenotype defined by longer fistula length, multiple skin openings and multiple fistulous tracts on MRI. These findings suggest that >2 fistula tracts and length >3.3 cm on pelvic MRI may be imaging features associated with abscess development and complications.